Multiplexed in vivo homology-directed repair and tumor barcoding enables parallel quantification of Kras variant oncogenicity - Ian P. Winters (Nature Portfolio, 2017)
Genome editing technologies enable the rapid interrogation of genetic alterations. Here, the authors present a CRISPR/Cas9-based platform to simultaneously investigate multiple activating point mutations in de novo cancers in mice; and generate panels of Kras-variants in different tissues to induce cancer.